AI-assisted programming using GitHub Copilot and ChatGPT for coding - Taulli, Tom (O'Reilly Media, Inc., 2024)
Get practical advice on how to leverage AI development tools for all stages of code creation, including requirements, planning, and design; coding; and debugging, testing, and documentation. With this practical book, beginners and experienced developers alike will learn how to use a wide range of tools, from general-purpose LLMs (ChatGPT, Bard, and Claude) to code-specific systems (GitHub Copilot, Tabnine, Cursor, and Amazon CodeWhisperer). You'll also learn about more specialized generative AI tools for tasks such as text-to-image creation. Author Tom Taulli provides a methodology for modular programming that aligns effectively with the way prompts create AI-generated code. This guide also describes the best ways of using general purpose LLMs to learn a programming language, explain code, or convert code from one language to another.
Keywords: ChatGPT; Git (Computer file); Computer programming; Natural language processing (Computer science); Artificial intelligence -- Computer programs; Programmation (Informatique); Traitement automatique des langues naturelles; Intelligence artificielle; Logiciels; computer programming